Excess Molar Enthalpies of Mixtures of Acetylene Tetrachloride with Dimethylsulfoxide, Acetone, Acetonitrile and N-Dibutyl Ether at 303.15 K - Tripathi, Atri D.; Choudhary, Shalini (Journal of Applied Solution Chemistry and Modeling, 2015)
The Excess molar enthalpies have been determined for binary liquid mixtures of acetylene tetrachloride (CHCl2CHCl2) (ATC) with dimethylsulfoxide, acetone, acetonitrile and n-dibutyl ether at the temperature 303.15 K by microcalorimetry. The excess molar enthalpies are negative for all the mixtures over the whole composition range. The results were fitted with the Redlich-Kister equation by means of the least square method. The values of HE decrease in the order: Dimethylsulphoxide > acetone>acetonitrile > dibutyl ether. The same decreasing trend was observed for calculated hydrogen bond energies of these systems. These results indicate the existence of specific interactions between all these components.